Minimum Wages, Wages, and Price Pass-Through: The Case of McDonald’s Restaurants - Ashenfelter, Orley; Jurajda, Štěpán (Journal of Labor Economics, 2022)
Based on 2016–20 hourly wage rates of McDonald’s basic crew and Big Mac prices collected simultaneously from almost all US McDonald’s, we find that in 25% of instances of minimum wage increases, restaurants keep constant their wage premium above the increasing minimum wage. Higher minimum wages are not associated with faster adoption of touch-screen ordering, and there is near-full price pass-through of minimum wages. Minimum wage hikes lead to increases in real wages (expressed as how many Big Macs 1 hour of basic crew work can buy) that are one-fifth lower than the corresponding increases in nominal wages.